Minat Siswa Dalam Mengikuti Ekstrakulikuler Olahraga di SMKS PGRI 1 Kota Sukabumi - Pakpahan, Ganda Arief Frans (Prodi Pendidikan Jasmani Kesehatan dan Rekreasi Universitas Muhammadiyah Sukabumi, 2023)
Physical education is a specific education, by doing physical activities that have been designed to achieve a complex goal so as to get a very important quality in the life of students. This study aims to determine how much student interest in extracurricular sports at SMKS PGRI 1 Kota Sukabumi. This study uses quantitative research methods. The population of this study were 30 students of SMKS PGRI 1 Kota Sukabumi who participated in extracurricular sports. By using saturated sampling technique. The results of this study indicate that 13 students with a percentage of 43.33% have an interest in extracurricular sports with a high category, 17 students with a percentage of 56.67% have an interest in extracurricular sports with a very high category, 0 students with a percentage of 0% have an extracurricular interest with a low category, as many as 0 students have very low extracurricular sports, Overall it can be concluded that the results of the survey of student interest in participating in extracurricular sports activities at SMKS PGRI 1 Kota Sukabumi are in the very high category with a percentage of 56.67%.